2013
DOI: 10.1002/chem.201203915
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Selectivity in the Binding of [4]Helicene Derivatives to Double‐Stranded DNA

Abstract: The interaction of a series of chiral cationic [4]helicene derivatives, which differ by their substituents, with double-stranded DNA has been investigated by using a combination of spectroscopic techniques, including time-resolved fluorescence, fluorescence anisotropy, and linear dichroism. Addition of DNA to helicene solutions results to a hypochromic shift of the visible absorption bands, an increase of fluorescence quantum yield and lifetime, a slowing down of fluorescence anisotropy decay, and a linear dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 67 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…Applications in several fields of chemistry can be foreseen, from bio-imaging to polarized emitting devices. [ 17,27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications in several fields of chemistry can be foreseen, from bio-imaging to polarized emitting devices. [ 17,27 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that 1 - 3 conserve a non-negligible fluorescence quantum yield in water (from 7% for 2 up to 10% for 3 ) which is of importance for possible uses as red bio-imaging probes. [ 5b,17 ]…”
Section: Absorption and Fluorescencementioning
confidence: 99%
“…Chiral cationic [4]helicenes 191 (Figure 19), having methoxy substituents at the innermost position, were also able to bind with DNA molecules, as evident from a noticeable change in absorption, fluorescence, and CD spectra obtained during the corresponding host-guest studies [102]. It was concluded that the molecular plane of the helicene dye lies essentially parallel to the DNA bases, implying intercalation mode rather than groove binding.…”
Section: Helicene-based Chiral Recognition Involving Biologically Relmentioning
confidence: 99%
“…Representative examples are heterohelicenium systems studied by Lacour group or helical dications called helquats developed by our group . These and similar cationic systems promise attractive range of properties and applications that may be complementary to non‐ionic helicenes. For example, they can strongly interact with their environment due to their positively charged helical skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can strongly interact with their environment due to their positively charged helical skeleton. Also, their solubility in aqueous media and electron‐accepting properties associated with their cationic nature can be advantageous.…”
Section: Introductionmentioning
confidence: 99%